A change in surgical margin: do wider surgical margins lead to decreased rates of local recurrence in T1 and T2 oral tongue cancer?. Issue 1 (January 2023) - Daniell, J.R.; Rowe, D.; Wiesenfeld, D.; McDowell, L.; Hall, K.A.; Nastri, A.; Iseli, T.A.; Wong, T.
Abstract: The purpose of this study was to assess the impact of a change in macroscopic/surgical margin width upon histological margins and loco-regional failure in early oral tongue squamous cell carcinoma (OTSCC). In 2009, the surgical margin protocol was increased from 10 mm to 15 mm. A retrospective review was performed of all patients who underwent treatment for early OTSCC between 2009 and 2016 with a 15-mm surgical margin ( n = 142), and these patients were compared to those treated between 1999 and 2008 with a 10-mm surgical margin ( n = 78). There was a significant increase in the rate of clear histological margins ( P < 0.001). The rates of close ( P = 0.002) and involved ( P < 0.001) histological margins decreased significantly. There were significant reductions in local ( P < 0.001) and regional ( P < 0.001) recurrence rates. This study demonstrated that a surgical margin of 15 mm delivered significantly lower rates of close/involved histological margins and improved local and regional disease recurrence in early OTSCC when compared with a surgical margin of 10 mm.